VALUASI EKONOMI SUMBERDAYA ALAM PADA DAS TIWORO KABUPATEN MUNA BARAT - Hasddin, Hasddin (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine; 1) Large use value, non-use value, and natural resource option value in the Tiworo watershed area; and 2) What is the total economic value generated in the Tiworo watershed area. The analysis technique used in this study consists of two, namely descriptive qualitative analysis (qualitative descriptive) and quantitative research. Quantitative analysis was carried out using the model: Productivity Method for Economic Value of Natural Resources in the Tiworo Watershed; Water residual value is done to estimate the economic value of water resources in the Tiworo watershed; and the Contingent Valuation Method (CVM) for Determining Tourism PAPs. The results of the study also show that the existing resources in the Tiworo watershed area are; a) Agriculture and plantations; b) Freshwater fisheries, c) Forestry; and d) Ecotourism. Based on the results of the valuation of the SDA Economy in the Tiworo watershed, use value is Rp. 459,563,876,989. Non-use value is Rp. 11,424,525,000. thus, a total economic value of Rp. 470,988,401,989 was obtained.